Español - Español, Español; Español, Español; Español, Español (Ars Pharmaceutica (Internet), 1991)
A serie of high popular take vegetable simples in West Andalucía, that for different reason they have attracted us: in some cases for the dose recommended, in other cases for the surprising therapeutics indications and composition of the sames are picked up.